235k views
4 votes
An equation is shown below:

(4x − 1) + (2x + 2) = 1

Which statement shows a correct next step in solving the equation?

The equation can become 6x + 1 = 1 by combining like terms.
The equation can become 3x + 4x = 1 by solving the terms in the brackets.
The equation can become 3x + 4x = 1 by applying the associative property of multiplication.
The equation can become 6x + 1 = 1 by applying the distributive property.

User Rootkit
by
6.5k points

2 Answers

1 vote
The equation can become 6x + 1 = 1 by combining like terms. :)
User Jolmos
by
5.9k points
4 votes

Answer with explanation:

The equation in one variable x, which we have to solve is:

(4x-1) +(2 x+2)=1

Adding like terms

→4 x +2 x +2-1=1

→6 x+1=1

→→Subtracting 1, from both sides

→6 x+1-1=1-1

→6 x=0

Dividing both sides by , 6 we get

x=0, is the solution of the above equation.

Option A:⇒ The equation can become 6x + 1 = 1 by combining like terms.

User Commadelimited
by
6.1k points